Factors Influencing the Game Players to Choose Chinese Online Games - Han, Fei (2010)
This study is carried out with the aim to propose recommendations to Chinese online game developers to maintain and improve its important features that intrigue the game players. By identifying factors influencing the game players to choose Chinese online games, findings of this research offer information to both academicians and practitioners to develop the product adaption or customization when Chinese online games are going to global. The identification of factors such as “personal killing” “combat system”, NPCs, crafting system, security system, dynamic contents and environment, social interaction, graphics and effects that game players provided in this study will assist the Chinese online developers to alter their product so that it can meet the customers’ demand in new market. The most important contribution of this study is the data collections from secondary and primary sources such as journal, articles, and academic books about Chinese online games in global market which were limited from the prior studies in this area.